How I treat disseminated intravascular coagulation - Levi, Marcel; Scully, Marie (Blood, 2018)
Disseminated intravascular coagulation (DIC) is a condition characterized by systemic activation of coagulation, potentially leading to thrombotic obstruction of small and midsize vessels, thereby contributing to organ dysfunction. At the same time, ongoing consumption of platelets and coagulation proteins results in thrombocytopenia and low concentrations of clotting factors, which may cause profuse hemorrhagic complications. DIC is always secondary to an underlying condition, such as severe infections, solid or hematologic malignancies, trauma, or obstetric calamities. A reliable diagnosis of DIC can be made through simple scoring algorithms based on readily available routine hemostatic parameters. The cornerstone of supportive treatment of this coagulopathy is management of the underlying condition. Additionally, administration of heparin may be useful, and restoration of physiological anticoagulants has been suggested, but has not been proven successful in improving clinically relevant outcomes so far. In patients with major bleeding or at risk for hemorrhagic complications, administration of platelet concentrates, plasma, or coagulation factor concentrates should be considered.